MISCLASSIFIKASI PASIEN DIABETES MELITUS TIPE 2 (T2DM) DI INDONESIA: TINJAUAN SISTEMATIS DENGAN METODE PRISMA - Zein, Eiska Rohmania; Sunindya, Bernadus Rudy (Politeknik Kesehatan Kemenkes Malang, 2025)
Type 2 diabetes mellitus (T2DM) is a major health problem in Indonesia, with a steadily increasing incidence. The high prevalence of undiagnosed cases and the occurrence of clinical and administrative misclassification pose significant challenges to health services, epidemiological research, and the national financing system. This study aims to review evidence related to the forms, causes, and impacts of T2DM misclassification in Indonesia using a systematic review approach using the PRISMA method, and to provide strategic recommendations for system improvement. A literature search was conducted in international and national databases using the PRISMA 2020 framework. Of the 456 articles identified, 35 were fully screened, and 9 met the inclusion criteria. Data were synthesized narratively due to methodological heterogeneity between studies. Misclassification of T2DM was found in three main areas. First, clinical misclassification occurs, particularly of LADA and MODY, which are often labeled as T2DM. Second, diagnostic overreliance on HbA1c without verification with OGTT or FPG, potentially resulting in false-positive or false-negative results. Third, administrative inaccuracies in ICD-10 coding affect claims, registries, and national reports. Furthermore, the large proportion of undiagnosed diabetes patients exacerbates data distortions and delays in treatment. Misclassification of T2DM in Indonesia is a multidimensional problem that impacts patients, healthcare professionals, and policymakers. An integrated strategy is needed, including strengthening diagnostic algorithms, training coders, electronic data audits, and expanding screening of high-risk populations to reduce misclassification and improve service quality.